Analisis Stabilitas Nilai Tukar Rupiah dalam Perspektif Ekonomi Syariah - Vina Septianingrum; Imahda Khoiri Furqon (FEBI UIN Sunan Kalijaga, 2025)
This study examines the factors affecting the stability of the Indonesian rupiah exchange rate and analyzes it from an Islamic economics perspective. In addition, the study discusses the concept of sharf (currency exchange) in Islam and explores the role of Islamic economic principles in supporting exchange rate stability. A qualitative approach with a library research method was employed. The study relies on secondary data collected from academic journals, books, official reports, and other relevant literature related to exchange rates and Islamic economics. The data were analyzed descriptively to identify the relationship between macroeconomic factors and the stability of the rupiah. The findings show that the stability of the rupiah is influenced by several key factors, including inflation, interest rates, export and import activities, and global geopolitical conditions. High inflation and excessive dependence on imports tend to weaken the rupiah, while stronger export performance contributes to exchange rate stability. From an Islamic economics perspective, exchange rate stability can be promoted through the prohibition of riba, gharar, and maysir, as well as through strengthening the real sector and implementing sharf transactions in accordance with Islamic principles. Therefore, Islamic economics offers a potential framework for supporting sustainable monetary stability and strengthening Indonesia’s economic resilience.